THE ROLE OF INNOVATION ACTIVITY IN STRATEGIC MARKETING AND ITS IMPACT ON ENTERPRISE DEVELOPMENT: THE CASE OF NETFLIX - KUSHCH, Anastasiia; LATYSHEV, Kostiantyn (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article comprehensively investigates the integration of innovation activity within the framework of strategic marketing and examines the pivotal role that strategic management plays in developing sustainable competitive advantages for enterprises amid digital transformation. It delves into the fundamental stages of the innovation process and outlines specific performance indicators that influence strategic decision-making. The paper argues that when innovation activity is aligned with strategic management principles, it becomes a vital element in ensuring long-term resilience, adaptability, and improved market positioning. Special attention is given to the interplay between innovation strategy, organizational flexibility, and digital capability. A significant focus is placed on the analytical tools and strategic frameworks that enable modern enterprises to effectively harness internal resources, evaluate dynamic market conditions, and respond to evolving customer needs. By fostering an innovation-driven culture, companies can create more value and enhance their responsiveness to change. The study presents the innovation strategy of Netflix as a detailed case study, illustrating the company’s adept use of artificial intelligence, personalized content delivery, and agility in adapting to shifting consumer behavior. These factors demonstrate how data-centric innovation strategies, continuous technological investment, and a strong customer orientation drive strategic success in competitive digital markets. The article further emphasizes the need for companies to pursue adaptive strategies that align with rapid technological developments and market shifts. It highlights the importance of cultivating a flexible organizational environment that supports experimentation and continuous learning. Ultimately, the study concludes that sustainable competitive advantage in the digital age depends on a company’s ability to systematically integrate innovation, leverage digital tools, and maintain strategic foresight in decision-making.